2013
DOI: 10.1128/aem.02865-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Plant Biomass Degradation by Thermophilic Fungus Myceliophthora heterothallica

Abstract: bRapid and efficient enzymatic degradation of plant biomass into fermentable sugars is a major challenge for the sustainable production of biochemicals and biofuels. Enzymes that are more thermostable (up to 70°C) use shorter reaction times for the complete saccharification of plant polysaccharides compared to hydrolytic enzymes of mesophilic fungi such as Trichoderma and Aspergillus species. The genus Myceliophthora contains four thermophilic fungi producing industrially relevant thermostable enzymes. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The cellulase production levels by the strains developed here from one transformation are comparable to those of strains engineered by time-consuming methods in the well-known cellulase production species T. reesei [55] and P. oxalicum [53], suggesting that strain engineering for cellulase production in M. thermophila could be improved significantly within a short time through the CRISPR/Cas9 system developed here. Additionally, this CRISPR/Cas9 system can be used without modification in other Myceliophthora species such as M. heterothallica [4143], indicating it could be potentially used in many thermophilic fungi. This broad applicability provides an opportunity for deep investigation of these fungi, some of which possess interesting features such as a sexual cycle, both for basic research and for possible novel host development for future industrial biotechnological use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellulase production levels by the strains developed here from one transformation are comparable to those of strains engineered by time-consuming methods in the well-known cellulase production species T. reesei [55] and P. oxalicum [53], suggesting that strain engineering for cellulase production in M. thermophila could be improved significantly within a short time through the CRISPR/Cas9 system developed here. Additionally, this CRISPR/Cas9 system can be used without modification in other Myceliophthora species such as M. heterothallica [4143], indicating it could be potentially used in many thermophilic fungi. This broad applicability provides an opportunity for deep investigation of these fungi, some of which possess interesting features such as a sexual cycle, both for basic research and for possible novel host development for future industrial biotechnological use.…”
Section: Discussionmentioning
confidence: 99%
“…Using this system, multiple strains with significantly increased lignocellulase production were generated. Successful targeted gene deletion was also demonstrated in M. heterothallica [4143], suggesting that the system developed here could be used in other thermophilic fungi. This new tool should accelerate the engineering of thermophilic fungi for industrial biotechnological production of enzymes and chemicals.…”
Section: Introductionmentioning
confidence: 93%
“…However, not all fungi are alike; some fungi, such as Trichoderma reesei and Aspergillus niger, employ predominantly a classical acid catalysis hydrolytic model of degrading plant cell wall polymers, while others, such as Myceliophthora thermophila (11,12) and Phanerochaete chrysosporium (13,14), appear to take advantage of an oxidative route of breaking down glycoside bonds. Even though some fungi predominantly hydrolyze biomass while others employ an oxidative mechanism, most fungi contain a mixed set of hydrolases and oxidases.…”
mentioning
confidence: 99%
“…The production of fruiting bodies had been observed originally for 68 this species by von Klopotek (1976), who described it as Thielavia heterothallica. The species 69 was placed in Myceliophthora by van den Brink et al (2012), who confirmed crossing behavior 70 and later presented evidence for recombination using AFLP analysis (van den Brink et al, 2013). 71…”
Section: Introduction 47mentioning
confidence: 91%